Classical and Reverse Substituent Effects in Substituted Anthrol Derivatives. Issue 1 (25th January 2019) - Szatylowicz, Halina; Domanski, Mateusz A.; Krygowski, Tadeusz M.
Abstract: The substituent effect in 1‐, 2‐, and 9‐anthrols is studied by means of B3LYP/6‐311++G(d, p) computation, taking into account substituents (X): NO2, CN, OH and NH2 located in all positions except the adjacent ones. The substituent effect is characterized by approaches based on quantum chemistry: The charge of the substituent active region (cSAR), substituent effect stabilization energy (SESE) and the charge flow index (CFI) describing flow of the charge from X to the fixed group (or vice versa) as well as substituent constants σ . Changes in properties observed in the fixed group (OH) are described by cSAR(OH). Mutual interdependences are found between these descriptors. The HOMA index is used to describe an effect of a substituent on aromaticity of an anthrol hydrocarbon skeleton and of individual rings. In all cases, the classical (influence of X on the properties of OH) and reverse (influence of OH on the properties of X) substituent effects are studied. The latter is clearly documented by the cSAR approach. Abstract : Give and take : How do differently located substituents on anthrol molecules affect the properties of the hydroxy group in three different anthracene positions (1, 2 and 9)? The charge of the substituent active region (cSAR) approach enables the study both classical and reverse substituent effects.